2013
DOI: 10.5294/aqui.2013.13.2.8
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of Alcoholic Beverages among Nursing Students

Abstract: RESUMoObjetivo: o consumo de bebidas alcoólicas entre os estudantes universitários tem se tornado uma preocupação crescente nos últi-mos anos, por isso este estudo foi desenvolvido com o objetivo de identificar o consumo dessa substância psicoativa entre estudantes de enfermagem. Método: trata-se de estudo epidemiológico descritivo do tipo transversal desenvolvido em uma universidade privada da cidade do Rio de Janeiro, Brasil, com 161 estudantes que responderam a um questionário autoaplicável que continha inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 11 publications
2
4
0
7
Order By: Relevance
“…A previous research identified similar results to this study, that is, suggesting that the university environment can favor the increased frequency of consumption of alcoholic beverages (4) .…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…A previous research identified similar results to this study, that is, suggesting that the university environment can favor the increased frequency of consumption of alcoholic beverages (4) .…”
Section: Discussionsupporting
confidence: 89%
“…There are a number of quantitative studies about this theme (1)(2)(3)(4)(5)(6)(7)(8)(12)(13)(14)(15)(16)(17)(18) . However, this research offers subsidies based on a qualitative perspective, from the perception of student leaders, broadening this discussion.…”
Section: Objectivementioning
confidence: 99%
See 1 more Smart Citation
“…A iniciação do uso de álcool pela maioria (56,18%) dos participantes da pesquisa deu-se antes ou (14) . e comportamento de risco, principalmente entre os jovens (15) .…”
Section: Discussionunclassified
“…Con respecto al consumo de alcohol, el 81,1% de la muestra lo ha consumido y ese porcentaje, en su mayoría, está constituido por mujeres. La alta prevalencia se puede observar en el estudio realizado en Lima Perú en el que se estudió a los alumnos del segundo año y obtuvieron un porcentaje mayor del 50%, mientras que en Río de Janeiro, Brasil, en una universidad privada fue del 67,7% y en Veracruz, México, fue de 66,7% 15,16,17 . Los estudiantes universitarios consumen alcohol por carencia de información correcta, estrés y falta de actividades recreativas, puesto que presentan una dificultad para relajarse y por ello recaen en el alcohol 16 .…”
Section: Discussionunclassified